Presentation of lacrimo-auriculo-dento-digital (LADD) syndrome in a young female patient - McKenna, G. J.; Burke, F. M.; Mellan, K. (European archives of paediatric dentistry, 2009)
BACKGROUND: Lacrimo-auriculo-dento-digital (LADD) syndrome (OMIM #149730) is an autosomal-dominant congenital disorder that can be caused by heterozygous mutations in the tyrosine kinase domains of the genes encoding fibroblast growth factor receptors 2 (FGFR2) and 3 (FGFR3), and has been found in association with a mutation in the FGF10 gene, which encodes an Fgfr ligand. Clinical signs vary, but the condition is characterised by involvement of the lacrimal and salivary systems, cup-shaped ears, hearing loss and dental abnormalities. Additional features may include involvement of the hands and feet with other body systems particularly the kidneys. CASE REPORT : Previous literature on the subject has been reviewed and this case is the first presentation of LADD syndrome in the Republic of Ireland, as a sporadic case in a 12-year-old girl who exhibited a range of dental and digital anomalies. TREATMENT : Her general medical practitioner managed her medical care whilst her oral care necessitated a multidisciplinary approach involving restorative and orthodontic elements. FOLLOWUP : The initial restorative phase of treatment has successfully improved the appearance of the patient ’s anterior teeth using direct resin composite build-ups.